2022
DOI: 10.3102/00346543221094081
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Teachers’ Knowledge and Attitudes Toward Bullying: A Systematic Review

Abstract: Preservice teachers will one day be responsible for addressing bullying among their students but their readiness to fulfill this critical role is unknown. This article addressed this line of inquiry by conducting a systematic review assessing preservice teachers’ knowledge, attitudes, sense of responsibility, and confidence to deal with bullying. A total of 42 studies met our inclusion criteria and were included in our review. Results suggest that few preservice teachers understand the hallmarks of bullying. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…Perspectives of teachers and school administrators on contract teaching in developing nations are typically similar. Labor and employment policies in education should be set up in a healthy approach in order for them to be applied efficiently (Dawes, 2022). The determination of employment relations in education is crucial, particularly when identifying the factors that affect the educational process and assessing the quality of the educational service.…”
Section: Discussionmentioning
confidence: 99%
“…Perspectives of teachers and school administrators on contract teaching in developing nations are typically similar. Labor and employment policies in education should be set up in a healthy approach in order for them to be applied efficiently (Dawes, 2022). The determination of employment relations in education is crucial, particularly when identifying the factors that affect the educational process and assessing the quality of the educational service.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study among 153 teachers in Pakistan showed that over half of the teachers (53.6%) lacked adequate knowledge about bullying in school, and struggled to recognize more subtle or indirect forms of bullying, such as emotional or relational bullying (Shamsi et al, 2019). Studies have also shown that compared with in-service teachers, preservice teachers' knowledge of bullying was even more limited (Dawes et al, 2022). Preservice teachers were less likely to identify the different types of bullying, and the roles individuals can play in bullying dynamics, than in-service teachers (Henry, 2020).…”
Section: Teachers' Beliefs About Bullyingmentioning
confidence: 99%
“…Studies have shown that teachers who lack sufficient knowledge about bullying or believe that bullying is a normal part of child development are less likely to adopt effective bullying strategies (Hektner & Swenson, 2012; Mishna et al, 2020). A review study showed that as future educators, most preservice teachers lack knowledge of bullying, and have difficulties identifying and intervening in bullying situations (Dawes et al, 2022). Few preservice teachers understood the hallmarks of bullying, and although most preservice teachers reported that they were concerned about bullying, some still believed it to be a normal part of growing up (Dawes et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study conducted by Dawes et al (2022) few preservice teachers understand the hallmarks of bullying. In terms of their attitudes toward bullying, most preservice teachers report they are concerned about bullying, but some still believe it to be a normal part of growing up.…”
Section: Problem Statementmentioning
confidence: 99%